A facile approach to transform stainless steel mesh into pH-responsive smart material1. Issue 18 (5th March 2015) - Yang, Fuchao; Guo, Zhiguang
<x xml:space="preserve">Abstract</x> A facile method for the preparation of smart pH-responsive interface based on stainless steel mesh.